2011
DOI: 10.1007/s11214-011-9829-1
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Stratosphere-Troposphere Coupling During Major Solar Eclipses from FORMOSAT-3/COSMIC Constellation

Abstract: Sudden tropospheric cooling and induced stratospheric warming were found during the 22 July 2009 total solar eclipse. Can the 22 July 2009 hallmark also be seen in other major solar eclipses? Here we hypothesize that the tropospheric cooling and the stratospheric warming can be predicted to occur during a major solar eclipse event. In this work we use the FORMOSAT-3/COSMIC (F3C) Global Positioning System (GPS) radio occultation (RO) data to construct eclipse-time temperature profiles before, during, and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The thermal contraction in the troposphere can induce warming in the upper troposphere and lower stratosphere (between 13 and 23 km altitudes), which is dynamically driven. Wang et al (2012) further examined the response of the RO temperature to the solar eclipses on 15 January 2010, 26 January 2009, 1 August 2008, and 22 September 2006 The results suggested that the characteristic stratosphere-troposphere coupling in the RO temperature profiles represent distinctive atmospheric responses to the solar eclipses.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal contraction in the troposphere can induce warming in the upper troposphere and lower stratosphere (between 13 and 23 km altitudes), which is dynamically driven. Wang et al (2012) further examined the response of the RO temperature to the solar eclipses on 15 January 2010, 26 January 2009, 1 August 2008, and 22 September 2006 The results suggested that the characteristic stratosphere-troposphere coupling in the RO temperature profiles represent distinctive atmospheric responses to the solar eclipses.…”
Section: Introductionmentioning
confidence: 99%
“…Since the successful launched of the FORMOSAT-3/COSMIC (F3C) satellite on 14 April 2006, the F3C satellite has provide very consistent monitoring of atmospheric temperatures below 40 km altitude for more than 7 years [2][3][4][5][6][7]. In this work use this 7 years of good temperature measurements to construct atmospheric temperature trends from surface to the 40-km altitude, covering troposphere and most of the stratosphere; and from the South Pole to the North Pole.…”
Section: Introductionmentioning
confidence: 99%